Caldera of Godean, Sleman, Yogyakarta: A Volcanic Geomorphology Review - Hartono, Hill Gendoet; Sudradjat, Adjat; Verdiansyah, Okki (Universitas Muhammadiyah Surakarta, 2017)
Godean hills is located approximately 10 km westward from the Yogyakarta City. The landscape of Godean hills and plains is affected by various factors, such as lithology, geological structure, and sub-aerial process. The purpose of this study was to reveal the landscape of Godean. The method consisted of field study, morphological variables assessment, rock sampling, and laboratory analysis. The results of field mapping indicated that the landscape of Godean Â is an isolated hill with a steep slope of >40Â° and an elevation of +231 m a.s.l, passed by the rivers flows from northeast to southwest that disembogue into the west part of Kulon Progo. The morphologhy of Godean hills varies including G. (Gunung/Mountain) So (+173 m amsl), G. Gede (+218 m a.s.l), G. Wungkal (+187 m a.s.l), G. Butak (+154 m a.s.l), and G. Berjo ( + 175 m a.s.l), dominated by the lithology of igneous rock, which is composed of porphyry andesite-microdiorite, pumice lapilli, and quartz rich lapilli-tuff. In addition, most of the igneous rocks have weathered and have been altered to clays, while the deposition from Merapi volcano formed a landscape with an altitude between +100â+150 m a.s.l surrounding Godean hills. Sentolo Formation was found in Kembang, Bantul, which is located approximately Â±5km in the south of the study area N93ÂºE/12Âº, Â while the distribution in the southwest and northeast relatively covers the Godean hills in curve shape. The results of the analysis provide information related with Godean landscape that it is the remains of the volcanic caldera, with various igneous rock types and volcaniclastics deposits, as well as endured the occurrences of hydrothermal alteration and mineralization. Further geophysical research is required to determine the configuration of igneous rocks under the earths surface.